2010
DOI: 10.1002/pc.21022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a phosphorus compound on the morphology, thermal properties, and flammability of polystyrene/MgAl‐layered double hydroxide nanocomposites

Abstract: Phosphorus, nitrogen-containing monomer, acryloxyethyl phenoxy phosphorodiethyl amidate (AEPPA), was synthesized and copolymerized with styrene (St). Nanocomposites of polystyrene and poly(St-co-AEPPA) with various amounts of Mg-Al layered double hydroxide (LDH) were then prepared by in situ bulk polymerization. Structure and morphology of the nanocomposites were investigated by Fourier transform infrared (FTIR), X-ray diffraction (XRD), and transmission electron microscopy (TEM). The nanocomposites were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
0
10
0
1
Order By: Relevance
“…They reported that the flame retardancy was improved by 50.6% for PS/Mg-Al LDH 5% composition. Enhanced thermal and flammability properties for the PS/LDH composites have also been conveyed by other researchers (Majoni 2015;Tai et al 2011). Adopting in situ thermal polymerization, Yeh et al (2004) prepared a series of PS/clay composites and inferred improved anticorrosive and thermal characteristics of the nanocomposites.…”
Section: Introductionmentioning
confidence: 90%
“…They reported that the flame retardancy was improved by 50.6% for PS/Mg-Al LDH 5% composition. Enhanced thermal and flammability properties for the PS/LDH composites have also been conveyed by other researchers (Majoni 2015;Tai et al 2011). Adopting in situ thermal polymerization, Yeh et al (2004) prepared a series of PS/clay composites and inferred improved anticorrosive and thermal characteristics of the nanocomposites.…”
Section: Introductionmentioning
confidence: 90%
“…Therefore, these compounds are the most suitable for application as fillers for polymer nanocomposites. [7][8][9][10][11][12][13][14][15] However, research articles about polymer nanocomposites based on polyolefin and layered double hydroxides are still relatively scarce. 16 Layered compounds are characterized by stacked layers (having thickness from one to several atoms), in which the atoms have strong bonds along the crystallographic axes a and b, and are stacked along the c-axis (basal axis).…”
Section: Introductionmentioning
confidence: 99%
“…[23] Some of these compounds can act as reactive FR and initiators simultaneously. [24] It should be also emphasized that compounds containing boron atoms play an important role in reducing the flammability of polymers. The action of these compounds is based on formation of a surface char layer to prevent the oxidation of carbon and to limit the access of oxygen.…”
Section: Introductionmentioning
confidence: 99%